2008
DOI: 10.1017/s0022215108001941
|View full text |Cite
|
Sign up to set email alerts
|

Myringostapediopexy and myringolenticulopexy in mastoid surgery

Abstract: When surgically feasible, the technique of myringolenticulopexy is a useful method of preserving serviceable hearing in single-stage mastoid cavity surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…The difference between the pre and post-operative PTA-ABG results was statistically significant (P<.001). Our results are similar to the results of myringostapediopexy of Cheang et al 10 In his patients (n=25) PTA-ABG pre-and post operatively were 28.25 dB and 24.7 dB. However our results are different from those of Dawes PJD.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The difference between the pre and post-operative PTA-ABG results was statistically significant (P<.001). Our results are similar to the results of myringostapediopexy of Cheang et al 10 In his patients (n=25) PTA-ABG pre-and post operatively were 28.25 dB and 24.7 dB. However our results are different from those of Dawes PJD.…”
Section: Discussionsupporting
confidence: 84%
“…Depending upon a number of factors it is generally found that the success of myringostapediopexy is rather variable, the post operative PTA-ABG being anywhere between 10 and 60 dB. 1 Merchant et al report that type 10 Our results however are different from those of natural myringostapediopexy (n=15) and surgical canal down myringostapediopexy (n=35) of Dawes who reports PTA ABG closure within 30 dB in 87.0% and 90.0% of his cases in these two groups respectively. Moustafa and Khalifa observed hearing results of simple myringostapediopexy technique in (n=145) and showed that only 10% of these cases achieved PTA-ABG closure of less than 30 dB.…”
Section: Discussionmentioning
confidence: 54%
“…Our results of postoperative ABG of 33 dB augurs well with the varied result of 10 to 60 dB reported in the medical literature for tympanoplasty type III. [5][6][7][8] We now present the hearing analyses in each subtype of tympanoplasty type III.…”
Section: Discussionmentioning
confidence: 99%
“…Varying results have been reported in the medical literature for type III tympanoplasty: postoperative air-bone gap (ABG) of anywhere between 10 and 60 dB. [5][6][7][8] We performed an in-depth analysis of the sparse literature on the subject of hearing reconstruction in cholesteatoma. 4,5,[9][10][11][12] These studies have variable parameters.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation